2011
DOI: 10.1007/s00595-009-4260-x
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation for end-stage liver disease with severe hepatopulmonary syndrome: Report of a case

Abstract: Hepatopulmonary syndrome (HPS) is a serious complication of terminal liver disease, which manifests as severe hypoxia without any pulmonary anatomic or functional causes. The precise indications for liver transplantation in patients with severe HPS also remain unclear. A 49-year old woman was referred to our department for investigation and management of liver cirrhosis with severe hypoxia (PaO(2), 38 mmHg). A pulmonary perfusion scintigram showed an intrapulmonary shunt ratio of 40%, confirming a diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The intrapulmonary vascular shunts are identified by contrast-enhanced transthoracic or esophageal echocardiography (qualitative) or radionuclide lung perfusion scanning, using 99m Tc-macroaggregated albumin with brain uptake to measure the shunt fraction (quantitative) 6,7. Although radioactive lung-scan is able to stratify the severity of HPS,6,8 contrast-enhanced echocardiogram is a more sensitive and noninvasive method for diagnosis of HPS. In addition, physical examination, clubbing fingers, is important to diagnosis HPS.…”
Section: Discussionmentioning
confidence: 99%
“…The intrapulmonary vascular shunts are identified by contrast-enhanced transthoracic or esophageal echocardiography (qualitative) or radionuclide lung perfusion scanning, using 99m Tc-macroaggregated albumin with brain uptake to measure the shunt fraction (quantitative) 6,7. Although radioactive lung-scan is able to stratify the severity of HPS,6,8 contrast-enhanced echocardiogram is a more sensitive and noninvasive method for diagnosis of HPS. In addition, physical examination, clubbing fingers, is important to diagnosis HPS.…”
Section: Discussionmentioning
confidence: 99%
“… 90 It may come to mind that living donor LT (LDLT) may be more suitable than deceased donor LT (DDLT) because of the advantages of immediate availability of graft and opportunity to stabilize patient before LT. 86 However, some reports have shown that complication rates are the same between LDLT and DDLT patients. 92 95 To improve survival after LT, patients who are on the waiting list should be screened properly, and adequate oxygen should be given. 89 It should be remembered that HPS patients who are not candidates for LT may be candidates for localized resection or coil embolization of the dilated pulmonary vessels as a palliative treatment.…”
Section: Treatmentmentioning
confidence: 99%
“… described 5% mortality in a series of 21 patients (5 LDLT, 16 DDLT), peritransplant hypoxemic respiratory failure in 24%, biliary complications in 38%, and bleeding or vascular complications in 29% patients. Reversal of HPS after LDLT has been well described, but the reports on LDLT in adults are confined to few case reports and a series . We report 100% survival in present series.…”
Section: Discussionmentioning
confidence: 45%